A focused review of short electrospun nanofiber preparation techniques for composite reinforcement - Usaid, Ahmed Shakil; Shukur, Hj. Abu Hassan; Mohd Yazid, Yahya; Mohd Ruzaimi, Mat Rejab (De Gruyter Open Ltd, 2022)
Short nanofibers have been of interest in preparing 3D porous structures, aerosol filters, and nanocomposites. These materials require nanofiber retrieval and application in short form with simultaneous control over aspect ratio. Electrospinning, conventionally, offers minimal control over short nanofiber yield as nonwoven mat is the default configuration of collected sample. High surface area to volume ratio nanofiber, however, can offer new vistas in material design if standardization of short nanofiber preparation practices, offering control over aspect ratio, can be attained. It will provide novel insights into design of tissue engineering scaffolds, filtration membranes, and nanocomposite properties. This work summarizes reported efforts to prepare short nanofiber through mechanical, chemical, material, and operational variables. It aims to provide comparative glance at attempts to control aspect ratio along with pros and cons of the adopted techniques. Lastly, discussion shares generalized conclusions and insights gathered while reviewing material and operational variables adopted for short nanofiber preparation.